Essential role of mitochondrial energy metabolism in Foxp3+ T‐regulatory cell function and allograft survival. Issue 6 (13th February 2015) - Beier, Ulf H.; Angelin, Alessia; Akimova, Tatiana; Wang, Liqing; Liu, Yujie; Xiao, Haiyan; Koike, Maya A.; Hancock, Saege A.; Bhatti, Tricia R.; Han, Rongxiang; Jiao, Jing; Veasey, Sigrid C.; et al.
ABSTRACT: Conventional T (Tcon) cells and Foxp3 + T‐regulatory (Treg) cells are thought to have differing metabolic requirements, but little is known of mitochondrial functions within these cell populations in vivo. In murine studies, we found that activation of both Tcon and Treg cells led to myocyte enhancer factor 2 (Mef2)‐induced expression of genes important to oxidative phosphorylation (OXPHOS). Inhibition of OXPHOS impaired both Tcon and Treg cell function compared to wild‐type cells but disproportionally affected Treg cells. Deletion of Pgc1α or Sirt3, which are key regulators of OXPHOS, abrogated Treg‐dependent suppressive function and impaired allograft survival. Mef2 is inhibited by histone/protein deacetylase‐9 (Hdac9), and Hdac9 deletion increased Treg suppressive function. Hdac9 ‐/‐ Treg showed increased expression of Pgc1α and Sirt3, and improved mitochondrial respiration, compared to wild‐type Treg cells. Our data show that key OXPHOS regulators are required for optimal Treg function and Treg‐dependent allograft acceptance. These findings provide a novel approach to increase Treg function and give insights into the fundamental mechanisms by which mitochondrial energy metabolism regulates immune cell functions in vivo. —Beier, U. H., Angelin, A., Akimova, T., Wang, L., Liu, Y., Xiao, H., Koike, M. A., Hancock, S. A., Bhatti, T. R., Han, R., Jiao, J., Veasey, S. C., Sims, C. A., Baur, J. A., Wallace, D. C., Hancock, W. W. Essential role of mitochondrial energy metabolism in Foxp3 + T‐regulatory cell function and allograft survival. FASEB J. 29, 2315‐2326 (2015). www.fasebj.org